Contingent Negative Variation and Working Memory Maintenance in Adolescents with Low and High Motor Competencies. (18th April 2018) - Ludyga, Sebastian; Herrmann, Christian; Mücke, Manuel; Andrä, Christian; Brand, Serge; Pühse, Uwe; Gerber, Markus
Abstract : Although it has been suggested that motor and cognitive development is interrelated, the link between motor competencies and neurophysiological indices of working memory operations has not yet been examined in adolescents. This study is aimed at comparing contingent negative variation and working memory performance between adolescents with low and high motor competencies. In eighty-two adolescents, motor competencies were assessed with the MOBAK-5 (basic motor competencies, 5th grade) test battery and a median split was performed on this variable to divide them into low and high performers. Additionally, all participants completed a Sternberg paradigm to assess working memory maintenance. The initial (iCNV) and terminal (tCNV) components of the contingent negative variation elicited by the cognitive task were recorded using electroencephalography. Higher working memory maintenance was found in adolescents with high motor competencies compared to those with low motor competencies. Cluster-based permutation testing further revealed increased iCNV in adolescents with higher motor competencies. In contrast, there was no difference in tCNV between groups. The findings suggest that high working memory maintenance and effective task preparation are both linked to high motor competencies. Thus, high performers on complex motor tasks seem to rely more on a proactive control strategy, which is optimal in tasks with high working memory demands.